g-C3N4-supported LiAlH4 composite material based on antisolvent method, preparation method and application
Patent Information
- Application Number
- CN202510355152.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-03-25
AI Technical Summary
[0004]本发明提出一种基于反溶剂法的g-C3N4负载LiAlH4复合材料、制备方法及应用,旨在解决现有技术中LiAlH4储氢材料放氢速度缓慢和可逆性差等问题
[0026] This invention presents a g-C3N4-supported LiAlH4 composite material prepared via an anti-solvent method. LiAlH4 is loaded onto g-C3N4 nanosheets in the form of nanoparticles, leveraging the high specific surface area of g-C3N4 to improve the material's hydrogen storage performance. Experimental data show that the composite material has a hydrogen release capacity of approximately 0.7 wt% before 150°C, with a slow hydrogen release rate. However, at approximately 150°C, it can release approximately 5.4 wt% of hydrogen gas within a few seconds, representing an improvement in hydrogen release rate compared to the original LiAlH4. The dehydrogenation activation energy is reduced to 113.24 kJ·mol⁻¹. -1 and 104.223 kJ·mol -1 Compared with unmodified LiAlH4, the kinetic performance of the second-step hydrogen desorption was improved.
Smart Images

Figure CN120440835B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy materials technology, specifically relating to a g-C3N4-supported LiAlH4 composite material based on the antisolvent method, its preparation method, and its application. Background Technology
[0002] In the field of new energy technology, hydrogen energy is considered an important component of future energy sources due to its high energy density and zero emissions. However, the storage and transportation of hydrogen has always been a key challenge restricting its widespread application. Traditional liquid and gaseous hydrogen storage methods suffer from low safety and high energy consumption. Therefore, solid-state hydrogen storage technology has attracted widespread attention due to its high hydrogen storage capacity and good safety.
[0003] LiAlH4, as a high-density solid-state hydrogen storage material, theoretically possesses a hydrogen storage density as high as 7.9 wt%, and its dehydrogenation temperature is relatively low, making it a highly promising candidate material for hydrogen storage. However, LiAlH4 faces challenges in practical applications due to its slow hydrogen desorption rate and poor reversibility, limiting its application in fields such as on-board hydrogen storage. In existing technologies, improving the hydrogen storage performance of LiAlH4 through nano-sizing and catalyst modification has been extensively studied. For example, nano-sizing of LiAlH4 through mechanical ball milling can improve its hydrogen desorption rate to some extent, but this method is complex, costly, and prone to agglomeration, making large-scale application difficult. Furthermore, patent literature (CN 118491553 A) discloses an N-rGO@NiCo / LiAlH4 composite material, in which NiCo catalyst is loaded onto an N-rGO substrate through hydrothermal synthesis and impregnation, reducing the initial hydrogen desorption temperature of LiAlH4 to 103℃ and exhibiting certain hydrogen desorption performance (e.g., 1.5 wt%) at low temperatures (e.g., 80℃). However, the preparation process of this method is complex, and the hydrogen release rate and high-temperature hydrogen release efficiency still need to be further improved. The second-step hydrogen release temperature of the material is relatively high, and the reversibility is still not ideal. Summary of the Invention
[0004] This invention proposes a g-C3N4-supported LiAlH4 composite material based on the antisolvent method, its preparation method, and its application, aiming to solve the problems of slow hydrogen release rate and poor reversibility of LiAlH4 hydrogen storage materials in the prior art.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a g-C3N4-supported LiAlH4 composite material based on the antisolvent method, characterized in that the composite material is named g-C3N4 / LiAlH4, the mass ratio of each component is in the range of g-C3N4:LiAlH4 = 1-5:5-10, and the macroscopic morphology of the composite material is solid nanoparticles with a particle size of 10-20 nm.
[0007] Furthermore, the mass ratio of each component is g-C3N4:LiAlH4=5:5.
[0008] Secondly, the present invention provides a method for preparing the above-mentioned composite material, comprising:
[0009] S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution through a needle filter to remove insoluble matter, forming solution A.
[0010] S2. Weigh g-C3N4 and dissolve it in diethyl ether. After ultrasonic treatment, solution B is formed.
[0011] S3. Mix solution A and solution B, and stir thoroughly to form solution C;
[0012] S4. Add n-pentane to a stainless steel cup. The ratio of n-pentane to solution C is 6-20:1. Use a semiconductor cooler to cool the n-pentane to -10-0℃.
[0013] S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, and adjust the power to keep the n-pentane liquid surface from fluctuating.
[0014] S6. Use a pipette to draw up solution C and add it dropwise to n-pentane while the ultrasonicator is on to form suspension D, while keeping the thermoelectric cooler on during the process.
[0015] S7. After the addition is complete, continue ultrasonic shearing dispersion;
[0016] S8. Centrifuge or filter the suspension D to obtain the precipitate;
[0017] S9. The precipitate was transferred to a tube furnace and vacuum dried at 30-60℃ for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
[0018] Furthermore, in S1, the molar ratio of LiAlH4 to anhydrous LiI is 10-30:1.
[0019] Furthermore, in S2, the ultrasonic treatment time is 0.5-3 hours.
[0020] Furthermore, in S5, the ultrasonic shearing and dispersion procedure is ultrasonic for 5-20 seconds, pause for 5-20 seconds, with a total duration of 10-30 minutes.
[0021] Furthermore, in S6, the dropping rate of solution C is 0.5-2 mL / min.
[0022] Furthermore, in S7, the duration of the ultrasonic shear dispersion is 5-10 minutes.
[0023] Furthermore, in S8, the centrifugation rate is 5000-10000 rpm.
[0024] Thirdly, the present invention provides the application of the above-mentioned composite material in the field of solid-state hydrogen storage.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0026] This invention presents a g-C3N4-supported LiAlH4 composite material prepared via an anti-solvent method. LiAlH4 is loaded onto g-C3N4 nanosheets in the form of nanoparticles, leveraging the high specific surface area of g-C3N4 to improve the material's hydrogen storage performance. Experimental data show that the composite material has a hydrogen release capacity of approximately 0.7 wt% before 150°C, with a slow hydrogen release rate. However, at approximately 150°C, it can release approximately 5.4 wt% of hydrogen gas within a few seconds, representing an improvement in hydrogen release rate compared to the original LiAlH4. The dehydrogenation activation energy is reduced to 113.24 kJ·mol⁻¹. -1 and 104.223 kJ·mol -1 Compared with unmodified LiAlH4, the kinetic performance of the second-step hydrogen desorption was improved.
[0027] This invention is the first to combine the antisolvent method with g-C3N4, a material with a high specific surface area. It utilizes the solubility difference between a good solvent (diethyl ether) and a poor solvent (n-pentane) to trigger an explosive nucleation process, achieving the nano-sizing and uniform loading of LiAlH4. The innovation of this preparation method lies in its simple and efficient process, avoiding complex operations such as traditional mechanical ball milling, while significantly improving the thermodynamic and kinetic properties of the material. XRD and TEM analyses further confirm that LiAlH4 nanoparticles grow attached to the surface of g-C3N4, with optimized lattice structure (such as peak shift caused by LiI doping), providing a novel thermodynamic modification pathway for improving the performance of hydrogen storage materials.
[0028] The g-C3N4 / LiAlH4 composite material prepared by the antisolvent method in this invention not only exhibits significant advantages in hydrogen storage capacity and hydrogen desorption rate, but also demonstrates good structural stability and thermodynamic modification potential. DSC testing shows a strong exothermic peak during the dehydrogenation process, indicating the profound thermodynamic influence of the antisolvent method combined with the g-C3N4 support on the material. In-situ XRD analysis further reveals the phase evolution of the material during rapid dehydrogenation, verifying its efficient hydrogen desorption mechanism. This comprehensive performance improvement makes this composite material promising for applications in solid-state hydrogen storage, providing a practical solution for the safety and efficiency of hydrogen energy storage and transportation.
[0029] Of course, implementing the various technical solutions of this invention does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other embodiments can be obtained from these drawings without creative effort.
[0031] Figure 1 The X-ray diffraction pattern of the g-C3N4 / LiAlH4 composite material prepared in Example 1;
[0032] Figure 2 SEM images of the g-C3N4 / LiAlH4 composite material obtained in Example 1 at different magnifications;
[0033] Figure 3 TEM image and elemental distribution analysis diagram of the g-C3N4 / LiAlH4 composite material prepared in Example 1;
[0034] Figure 4 The graph shows the non-isothermal hydrogen desorption performance of the g-C3N4 / LiAlH4 composite material prepared in Example 1.
[0035] Figure 5 The temperature changes and hydrogen gas chromatography-mass spectra of the g-C3N4 / LiAlH4 composite material prepared in Example 1 at heating rates of 3K / min, 5K / min, and 10K / min are shown.
[0036] Figure 6 The Kissinger equation was linearly fitted to the g-C3N4 / LiAlH4 composite material prepared in Example 1.
[0037] Figure 7The mass spectrometry signal of the g-C3N4 / LiAlH4 composite material prepared in Example 1;
[0038] Figure 8 Differential thermal scanning signal of g-C3N4 / LiAlH4 composite material prepared in Example 1;
[0039] Figure 9 The in-situ X-ray diffraction pattern of the g-C3N4 / LiAlH4 composite material prepared in Example 1 at 30℃-250℃ is shown. Detailed Implementation
[0040] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings. Similar elements in different embodiments are referred to by associated similar element reference numerals. In the following embodiments, many details are described to facilitate a better understanding of this application. However, those skilled in the art will readily recognize that some features may be omitted in different situations, or may be replaced by other elements, materials, or methods. In some cases, certain operations related to this application are not shown or described in the specification. This is to avoid obscuring the core parts of this application with excessive description. For those skilled in the art, detailed description of these related operations is not necessary; they can fully understand the related operations based on the description in the specification and general technical knowledge in the art.
[0041] Furthermore, the features, operations, or characteristics described in the specification can be combined in any suitable manner to form various embodiments. At the same time, the steps or actions in the method description can be rearranged or adjusted in a manner obvious to those skilled in the art. Therefore, the various orders in the specification and drawings are only for the clear description of a particular embodiment and do not imply a necessary order, unless otherwise stated that a particular order must be followed.
[0042] This invention presents a method for preparing LiAlH4 nanoparticles loaded onto g-C3N4 nanosheets using an antisolvent method, successfully obtaining nanoparticles with a size of approximately 20 nm and achieving second-level rapid hydrogen release from the hydrogen storage material. Before 150°C, the hydrogen release rate is very slow, with a release capacity of approximately 0.7 wt%. However, when the temperature reaches approximately 150°C, the hydrogen release rate increases dramatically, releasing approximately 5.4 wt% of gas within a few seconds. This invention demonstrates significant advantages in both hydrogen storage capacity and hydrogen release efficiency, providing a new solution for the development of solid-state hydrogen storage technology.
[0043] The following are explanations of some of the terms involved in this invention:
[0044] LiAlH4: Lithium aluminum hydride;
[0045] g-C3N4: Graphitic carbon nitride.
[0046] This invention provides a g-C3N4-supported LiAlH4 composite material based on an anti-solvent method, its preparation method, and its application. The preparation method of this composite material is summarized as follows:
[0047] The composite material prepared by loading LiAlH4 onto g-C3N4 using the anti-solvent method is named g-C3N4 / LiAlH4. The mass ratio of each component is in the range of g-C3N4:LiAlH4 = 1-5:5-10. The macroscopic morphology of the composite material is solid nanoparticles.
[0048] The resulting composite material exhibits advantages such as rapid hydrogen release and thermodynamic optimization, making it widely applicable in solid-state hydrogen storage materials. Specifically, it can be used in scenarios such as on-board fuel cell hydrogen supply modules, portable power devices, and buffer materials for stationary hydrogen storage stations.
[0049] The present invention will be further illustrated below through several specific embodiments:
[0050] Example 1:
[0051] A method for preparing g-C3N4-supported LiAlH4 composite material based on antisolvent method includes the following steps:
[0052] S1. Weigh out LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution using a needle filter to remove insoluble matter, forming solution A, in which the molar ratio of LiAlH4 to anhydrous LiI is 20:1.
[0053] S2. Weigh g-C3N4 and dissolve it in diethyl ether. After sonication for 1 hour, solution B is formed.
[0054] S3. Mix solution A and solution B, and stir thoroughly to form solution C;
[0055] S4. Add n-pentane to a stainless steel cup, with the ratio of n-pentane to solution C being 15:1. Use a semiconductor cooler to cool the n-pentane to 0°C.
[0056] S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, adjust the power to keep the n-pentane liquid surface from fluctuating, the ultrasonic shear dispersion program is 15 seconds of ultrasonication, 15 seconds of pause, and a total duration of 10 minutes.
[0057] S6. Use a pipette to draw up solution C and add it dropwise to n-pentane while the sonication is on to form suspension D, while keeping the thermoelectric cooler on during the process;
[0058] S7. After the addition is complete, continue ultrasonic shearing dispersion for 5 minutes;
[0059] S8. The suspension D was centrifuged at 8000 rpm to obtain the precipitate;
[0060] S9. The precipitate was transferred to a tube furnace and vacuum dried at 45°C for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
[0061] In this embodiment, the mass ratio of each component of the composite material is g-C3N4:LiAlH4=5:5, and the macroscopic morphology of the composite material is solid nanoparticles.
[0062] To determine the phase structure of the composite material prepared in this embodiment, the substances contained in the material were characterized by XRD, such as... Figure 1 As shown, the most prominent peak in the material is the peak of LiAlH4, corresponding to the standard PDF card (PDF#12-0473). In addition, the characteristic peaks of g-C3N4 are well preserved, with the peak at 12.1° corresponding to the (100) crystal plane of g-C3N4, and the peak at 27° corresponding to the (002) crystal plane of g-C3N4, coinciding with the diffraction peak of LiAlH4. Furthermore, a diffraction peak at 25.6° corresponding to the (111) crystal plane of LiI and a diffraction peak at 52.8° corresponding to the (111) diffraction plane of the material were also found. For the region with angles greater than 50°, the corresponding material diffraction peaks, upon retrieval, are mainly associated with LiAl2H7 and LiAl4H. 13 This match is unprecedented in previous material synthesis studies. Furthermore, considering the individual peaks, compared to the standard PDF card, some peaks in the material show a shift to higher angles. This is speculated to be due to the addition of a small amount of LiI, which, during dissolution and recrystallization, enters the crystal lattice, affecting the lattice spacing and potentially influencing the thermodynamic properties. Similar effects have been reported in other aluminum hydrides.
[0063] Figure 2 This is a scanning electron microscope (SEM) image of the g-C3N4 / LiAlH4 composite sample prepared in this embodiment. Without self-degeneration of hydrogen, the sample did not exhibit widespread agglomeration; the aggregates were approximately 10 μm in size. At high magnification, the g-C3N4 exhibited a plate-like morphology and formed micron-sized flower-like structures through self-assembly. Furthermore, no significant loaded particles were found within the material, suggesting that the LiAlH4 adhered to the surface g-C3N4. Further transmission electron microscopy (TEM) is needed to determine the particle size, but it is clear that the LiAlH4 particles are relatively small.
[0064] The morphology and particle size of the composite material were observed using aberration-corrected transmission electron microscopy (TEM) images. Figure 3 As shown, Figure 3 (a) shows the morphology of LiAlH4 nanoparticles under transmission electron microscopy. Aggregation of small particles is clearly visible at the particle edges, while at higher magnification... Figure 3 (g) The size of the nanoparticles is clearly distinguishable, with particle sizes ranging from 10 to 20 nm. At high resolution, the lattice fringes of the material correspond to the (003) crystal plane of LiAlH4. Notably, due to the material's sensitivity to irradiation, a significant amorphization trend occurs at the particle edges, indicating that the actual particle size is smaller than shown in the image. Furthermore, diffraction rings of amorphous material are observed on the diffraction spot. Elemental distribution analysis suggests that the nanoparticles are formed by growth attached to the surface of g-C3N4.
[0065] Hydrogen storage performance of composite material samples was tested. Figure 4 The results show that the hydrogen desorption rate of the g-C3N4 / LiAlH4 sample is very slow before reaching 150℃, with a hydrogen desorption capacity of approximately 0.7 wt%. However, when the temperature reaches approximately 150℃, the hydrogen desorption rate increases dramatically, releasing approximately 5.4 wt% of gas within a few seconds. During the dehydrogenation process, the material releases a large amount of heat, causing the temperature in the reactor to rise sharply from 150℃ to approximately 170℃. The theoretical capacity of this material is no more than 4 wt%, but the actual hydrogen desorption capacity can only be matched by considering the total hydrogen storage capacity of LiAlH4 (10.5 wt%). However, in general, hydrogen desorption from LiH requires extremely high temperatures, approximately 650℃. Therefore, the actual hydrogen desorption pathway of the g-C3N4 / LiAlH4 sample needs further investigation, and it is expected that the antisolvent loading method has a significant impact on the thermodynamic properties of the material.
[0066] To further understand the dehydrogenation kinetics of the composite material g-C3N4 / LiAlH4 prepared in this embodiment, the kinetics of these two materials were investigated using mass spectrometry coupled with a temperature-programmed heating method. The materials were heated at heating rates of 3 K / min, 5 K / min, and 10 K / min, and data were recorded. The point of maximum hydrogen desorption rate was found using the mass spectrometry signal, and the activation energy of the reaction was calculated using the Kissinger equation. Figure 5 and 6 As shown, the g-C3N4 / LiAlH4 sample exhibited two distinct hydrogen desorption peaks under mass spectrometry. Activation energies were fitted to these peaks; the activation energy for the first step was approximately 113.24 kJ / mol, and for the second step, it was 104.223 kJ / mol. Compared to the original material, the first activation energy remained almost unchanged, but the second activation energy showed a slight decrease. Therefore, the antisolvent method, regardless of the presence or absence of a catalyst, can significantly reduce the activation energy of the material, thereby improving its kinetic properties.
[0067] To further understand the changes in the g-C3N4 / LiAlH4 composite sample prepared in this embodiment during the dehydrogenation process, differential scanning calorimetry (DSC) was used to investigate the thermal changes of the material from room temperature to 300°C. Simultaneously, mass spectrometry was used to test the purity of the released gas to ensure that the assessment of the material's hydrogen storage capacity was not interfered with by other gases. In the DSC test, an aluminum crucible was selected, and argon was used as the inert carrier gas. Figure 7 Possible impurity gases were identified, including ammonia, methane, and nitrogen. Mass spectrometry signals indicated that these impurity gases were not detected during the material's dehydrogenation process. Meanwhile, Figure 8 The DSC test results showed a strong exothermic peak during the dehydrogenation process, a phenomenon observed for the first time and not reported in any previous studies. The high exothermic peak in the DSC indicates that thermodynamic modification of the material was achieved through an antisolvent-based experimental approach combined with g-C3N4 nanosheets.
[0068] To better understand the phase changes of the composite material g-C3N4 / LiAlH4 sample prepared in this embodiment during the entire hydrogen release process, in-situ XRD was used to investigate the phase changes of the material during the heating process. The tests were conducted using a self-made in-situ XRD hydrogen storage tester. To prevent oxidation of the material during transfer, the sample was pressed into a glove box and sealed with Cape Town tape. Helium gas was continuously introduced into the box during the test to avoid interference from argon gas on X-ray absorption. Figure 9 As shown, the diffraction peaks of LiAlH4 dominate the material within the initial temperature range of 30℃-100℃, indicating that LiAlH4 maintains temperature stability within this range. In the 100℃-140℃ range, the material begins partial dehydrogenation, producing a certain amount of Li3AlH6, with some enhancement of the diffraction peaks of Al at 38° and 44°. At 143℃, the LiAlH4 peaks are still present, although their intensity is slightly reduced compared to the initial state. At 146℃, the LiAlH4 peaks completely disappear, while the intensity of the Al peaks increases, showing a break compared to 143℃. From 143℃ to 250℃, the initially produced Li3AlH6 gradually dehydrogenates and eventually disappears. Analyzing the entire dehydrogenation process, it can be mainly divided into two parts: most of the material has a smaller particle size and undergoes rapid dehydrogenation at 143℃, while the other part follows the original LiAlH4 dehydrogenation steps. The XRD results match the temperature-dependent dehydrogenation performance, showing rapid dehydrogenation within 3℃. Because the dehydrogenation of materials is a relatively rapid process, it is completed within the XRD scanning timeframe, making it impossible to discern the phase changes of the material during dehydrogenation.
[0069] In this embodiment, a g-C3N4 / LiAlH4 composite material prepared by the antisolvent method was successfully prepared, achieving the loading of LiAlH4 nanoparticles (10-20 nm) onto g-C3N4. This composite material exhibited hydrogen desorption performance, releasing 5.4 wt% hydrogen gas within seconds at 150 °C. The activation energy for the second dehydrogenation step was reduced to 104.223 kJ / mol, indicating improved kinetic performance. XRD, TEM, and DSC analyses showed that the antisolvent method combined with the g-C3N4 support optimized the structure and thermodynamic properties of the material, providing experimental evidence for the research of solid-state hydrogen storage materials.
[0070] Example 2:
[0071] This embodiment provides a method for preparing g-C3N4-supported LiAlH4 composite material based on the antisolvent method, including the following steps:
[0072] S1. Weigh out LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution using a needle filter to remove insoluble matter, forming solution A, in which the molar ratio of LiAlH4 to anhydrous LiI is 10:1.
[0073] S2. Weigh g of C3N4 and dissolve it in diethyl ether. After sonication for 0.5 hours, solution B is formed.
[0074] S3. Mix solution A and solution B, and stir thoroughly to form solution C;
[0075] S4. Add n-pentane to a stainless steel cup, with the ratio of n-pentane to solution C being 12:1. Use a semiconductor refrigerator to cool the n-pentane to -5℃.
[0076] S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, adjust the power to keep the n-pentane liquid surface from fluctuating, the ultrasonic shear dispersion program is 10 seconds of ultrasonication, 10 seconds of pause, and a total duration of 15 minutes.
[0077] S6. Use a pipette to draw up solution C and add it dropwise to n-pentane while the sonication is on to form suspension D, while keeping the thermoelectric cooler on during the process;
[0078] S7. After the addition is complete, continue ultrasonic shearing dispersion for 8 minutes;
[0079] S8. Centrifuge the suspension D at 5000 rpm to obtain the precipitate;
[0080] S9. The precipitate was transferred to a tube furnace and vacuum dried at 50°C for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
[0081] In this embodiment, the mass ratio of the components of the composite material is g-C3N4:LiAlH4=4:6, and the macroscopic morphology of the composite material is solid nanoparticles.
[0082] Example 3:
[0083] This embodiment provides a method for preparing g-C3N4-supported LiAlH4 composite material based on the antisolvent method, including the following steps:
[0084] S1. Weigh out LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution using a needle filter to remove insoluble matter, forming solution A, in which the molar ratio of LiAlH4 to anhydrous LiI is 30:1.
[0085] S2. Weigh g of C3N4 and dissolve it in diethyl ether. After sonication for 2 hours, solution B is formed.
[0086] S3. Mix solution A and solution B, and stir thoroughly to form solution C;
[0087] S4. Add n-pentane to a stainless steel cup. The ratio of n-pentane to solution C is 17:1. Use a semiconductor cooler to cool the n-pentane to -7℃.
[0088] S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, adjust the power to keep the n-pentane liquid surface from fluctuating, the ultrasonic shear dispersion program is 20 seconds of ultrasonication, 20 seconds of pause, and a total duration of 20 minutes.
[0089] S6. Use a pipette to draw up solution C and add it dropwise to n-pentane while the sonication is on to form suspension D, while keeping the thermoelectric cooler on during the process;
[0090] S7. After the addition is complete, continue ultrasonic shearing dispersion for 10 minutes;
[0091] S8. The suspension D was centrifuged at 6000 rpm to obtain the precipitate;
[0092] S9. The precipitate was transferred to a tube furnace and vacuum dried at 40°C for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
[0093] In this embodiment, the mass ratio of each component of the composite material is g-C3N4:LiAlH4=3:7, and the macroscopic morphology of the composite material is solid nanoparticles.
[0094] Example 4:
[0095] This embodiment provides a method for preparing g-C3N4-supported LiAlH4 composite material based on the antisolvent method, including the following steps:
[0096] S1. Weigh out LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution using a needle filter to remove insoluble matter, forming solution A, in which the molar ratio of LiAlH4 to anhydrous LiI is 10:1.
[0097] S2. Weigh g of C3N4 and dissolve it in diethyl ether. After sonication for 0.5 hours, solution B is formed.
[0098] S3. Mix solution A and solution B, and stir thoroughly to form solution C;
[0099] S4. Add n-pentane to a stainless steel cup. The ratio of n-pentane to solution C is 6:1. Use a semiconductor cooler to cool the n-pentane to -9℃.
[0100] S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, adjust the power to keep the n-pentane liquid surface from fluctuating, the ultrasonic shear dispersion program is 8 seconds of ultrasonication, 8 seconds of pause, and a total duration of 12 minutes.
[0101] S6. Use a pipette to draw solution C and add it dropwise to n-pentane at a rate of 0.5 mL / min during the ultrasonic treatment to form suspension D, while keeping the thermoelectric cooler on during this process;
[0102] S7. After the addition is complete, continue ultrasonic shearing dispersion for 5 minutes;
[0103] S8. After filtration of suspension D, a precipitate is obtained; filtration is carried out using a microporous membrane with a pore size of 0.22-0.45 μm under a vacuum of 0.01-0.08 MPa for 5-15 minutes.
[0104] S9. The precipitate was transferred to a tube furnace and vacuum dried at 30°C for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
[0105] The composite material prepared in this embodiment is named g-C3N4 / LiAlH4, with a mass ratio of g-C3N4:LiAlH4 = 1:10. The macroscopic morphology of the composite material is solid nanoparticles.
[0106] Example 5:
[0107] This embodiment provides a method for preparing g-C3N4-supported LiAlH4 composite material based on the antisolvent method, including the following steps:
[0108] S1. Weigh out LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution using a needle filter to remove insoluble matter, forming solution A, in which the molar ratio of LiAlH4 to anhydrous LiI is 30:1.
[0109] S2. Weigh g of C3N4 and dissolve it in diethyl ether. After sonication for 3 hours, solution B is formed.
[0110] S3. Mix solution A and solution B, and stir thoroughly to form solution C;
[0111] S4. Add n-pentane to a stainless steel cup, with the ratio of n-pentane to solution C being 20:1. Use a semiconductor cooler to cool the n-pentane to -1℃.
[0112] S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, adjust the power to keep the n-pentane liquid surface from fluctuating, the ultrasonic shear dispersion program is 20 seconds of ultrasonication, 20 seconds of pause, and a total duration of 30 minutes.
[0113] S6. Use a pipette to draw solution C and add it dropwise to n-pentane at a rate of 2 mL / min during the ultrasonication process to form suspension D, while keeping the thermoelectric cooler on.
[0114] S7. After the addition is complete, continue ultrasonic shearing dispersion for 10 minutes;
[0115] S8. The suspension D was centrifuged at 10,000 rpm to obtain the precipitate;
[0116] S9. The precipitate was transferred to a tube furnace and vacuum dried at 60°C for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
[0117] The composite material prepared in this embodiment is named g-C3N4 / LiAlH4, with a mass ratio of g-C3N4:LiAlH4 = 5:5. The macroscopic morphology of the composite material is solid nanoparticles.
[0118] The above examples illustrate the present invention only to aid in understanding it and are not intended to limit the scope of the invention. Those skilled in the art can make various simple deductions, modifications, or substitutions based on the principles of this invention.
Claims
1. A g-C3N4-supported LiAlH4 composite material based on the antisolvent method, characterized in that, The composite material is named g-C3N4 / LiAlH4, and the mass ratio of each component is in the range of g-C3N4:LiAlH4=1-5:5-10. The macroscopic morphology of the composite material is solid nanoparticles with a particle size of 10-20nm. The method for preparing the composite material includes: S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution through a needle filter to remove insoluble matter, forming solution A. S2. Weigh g-C3N4 and dissolve it in diethyl ether. After ultrasonic treatment, solution B is formed. S3. Mix solution A and solution B, and stir thoroughly to form solution C; S4. Add n-pentane to a stainless steel cup. The ratio of n-pentane to solution C is 6-20:
1. Use a semiconductor cooler to cool the n-pentane to -10-0℃. S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, and adjust the power to keep the n-pentane liquid surface from fluctuating. S6. Use a pipette to draw up solution C and add it dropwise to n-pentane while the ultrasonicator is on to form suspension D, while keeping the thermoelectric cooler on during the process. S7. After the addition is complete, continue ultrasonic shearing dispersion; S8. Centrifuge or filter the suspension D to obtain the precipitate; S9. The precipitate was transferred to a tube furnace and vacuum dried at 30-60℃ for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
2. The g-C3N4-supported LiAlH4 composite material obtained by the antisolvent method according to claim 1, characterized in that, The mass ratio of each component is g-C3N4:LiAlH4=5:
5.
3. The method for preparing the composite material according to claim 1 or 2, characterized in that, include: S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in diethyl ether. After stirring thoroughly, filter the solution through a needle filter to remove insoluble matter, forming solution A. S2. Weigh g-C3N4 and dissolve it in diethyl ether. After ultrasonic treatment, solution B is formed. S3. Mix solution A and solution B, and stir thoroughly to form solution C; S4. Add n-pentane to a stainless steel cup. The ratio of n-pentane to solution C is 6-20:
1. Use a semiconductor cooler to cool the n-pentane to -10-0℃. S5. Insert the ultrasonic shear disperser 1-2 cm below the surface of the n-pentane liquid, turn on the ultrasonic shear dispersion, and adjust the power to keep the n-pentane liquid surface from fluctuating. S6. Use a pipette to draw up solution C and add it dropwise to n-pentane while the ultrasonicator is on to form suspension D, while keeping the thermoelectric cooler on during the process. S7. After the addition is complete, continue ultrasonic shearing dispersion; S8. Centrifuge or filter the suspension D to obtain the precipitate; S9. The precipitate was transferred to a tube furnace and vacuum dried at 30-60℃ for 12 hours to obtain g-C3N4-supported LiAlH4 composite material.
4. The method for preparing the composite material according to claim 3, characterized in that, In S1, the molar ratio of LiAlH4 to anhydrous LiI is 10-30:
1.
5. The method for preparing the composite material according to claim 3, characterized in that, In S2, the ultrasonic treatment time is 0.5-3 hours.
6. The method for preparing the composite material according to claim 3, characterized in that, In S5, the ultrasonic shearing and dispersion procedure is ultrasonic for 5-20 seconds, pause for 5-20 seconds, with a total duration of 10-30 minutes.
7. The method for preparing the composite material according to claim 3, characterized in that, In S6, the dropping rate of solution C is 0.5-2 mL / min.
8. The method for preparing the composite material according to claim 3, characterized in that, In S7, the duration of the ultrasonic shear dispersion is 5-10 minutes.
9. The method for preparing the composite material according to claim 3, characterized in that, In S8, the centrifugation rate is 5000-10000 rpm.
10. The application of the composite material according to any one of claims 1-2 or the composite material prepared by the preparation method according to any one of claims 3-9 in the field of solid-state hydrogen storage.
Citation Information
Patent Citations
N-rGO-coated NiCo catalyst loaded LiAlH4 composite material, preparation method and application
CN118491553A
Fluorinated graphene coated magnesium borohydride composite hydrogen storage material, preparation method and application
CN113493188A
Graphite-phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material as well as preparation method and application thereof
CN116768151A